Comparative Study of Conditions for the Purpose of Guarantee in Mudarabah Contracts Perspective of Islamic Jurisprudence and Iran's Civil Law - Azizi, Bijan Haji; Younesi, Marzieh (Fakultas Syariah dan Hukum, UIN Syarif Hidayatullah Jakarta, 2019)
AbstractContract for practical investment are made in two forms, direct and indirect. Both of the contracts havedifferentiation so does the guaranteed interest condition for them. In the first method, which is the interest of direct investment, the owner of the capital is an investment agentand only interested investors are determined in terms and conditions. In this case from investment, interest is guaranteed by the fact that the investment recipient is committed to buy products produced at price that guarantee logical interest for investors. The accuracy of this guarantee condition is to ensure in term of Islamic law and jurisprudence because commitment to purchase is necessary condition. However in the second form, unlike the first, investor interest is indirectly decided and guaranteed and conditions are increasingly attractive by carrying out industrial and manufacturing activities. This form of interest is also considered legal and valid both in Islamic law and Iran's Civil Law and practically based on the principles of conditions and article 234 of Iran's civil law. So, the main problem of this research the validityof the guaranteed interest conditions in Iranian jurisprudence and law.Keywords: Guaranteed Profit Conditions, Jurisprudence, Iranian Law, MudarabahAbstrakKontrak untuk investasi praktis dibuat dalam dua bentuk, baik langsung maupun tidak langsung. Kedua metode investasi ini memiliki perbedaan, dan kondisi bunga yang dijamin untuk mereka juga akan berbeda. Pada metode pertama, yang merupakan bunga investasi langsung, pemilik modal adalah agen investasi, dan hanya bagi investor yang tertarik ditentukan dalam syarat dan ketentuan. Dalam hal investasi, bunga dijamin dengan fakta bahwa penerima investasi berkomitmen untuk membeli produk yang diproduksi dengan harga yang terjamin. Kondisi jaminan ini dipastikan baik dari segi hukum dan yurisprudensi Islam, karena adanya komitmen untuk membeli adalah syarat mutlak yang diperlukan. Namun dalam bentuk kedua, tidak seperti yang pertama, minat investor secara tidak langsung diputuskan dan dijamin dan kondisinya semakin menarik dengan melakukan kegiatan industri dan manufaktur. Bentuk minat ini juga dianggap sah, baik dalam hukum Islam dan Hukum Perdata Iran, serta sangat praktis berdasarkan pada prinsip-prinsip kelayakan dan pasal 234 hukum sipil Iran. Jadi, pertanyaan utama dari penelitian ini adalah seberapa validkah kondisi bunga yang dijamin dalam yurisprudensi dan hukum Iran?Kata kunci: Kondisi Keuntungan Terjamin, Yurisprudensi, Hukum Iran, MudarabahАннотацияКонтракты на практические инвестиции заключаются в двух формах - прямых и посредственных. У этих двух инвестиционных методов есть различия, и условия гарантированного процента для них также отличаются. В первом методе, который представляет интерес прямых инвестиций, владелец капитала также является инвестиционным агентом, и только заинтересованные инвесторы определяются по положениям и условиям. В случае инвестиций, интерес гарантируется тем фактом, что получатель инвестиций стремится покупать продукты, произведенные по гарантированным ценам. Условия данной гарантии обеспечиваются с точки зрения исламского права и исламской юриспруденции, поскольку обязательство по покупке является необходимым условием. Но во второй форме, в отличие от первой, заинтересованность инвестора определяется и гарантируется посредственным образом, а условия становятся все более привлекательными при осуществлении промышленной и производственной деятельности. Эта форма также считается законной и действительной как в исламском праве, так и в гражданском праве Ирана и практически основана на принципах обладания правом и статье 234 гражданского права Ирана. Итак, главный вопрос этого исследования состоит в том, насколько верны условия гарантированного интереса в иранской юриспруденции и Иранском праве.Ключевые слова: условия гарантированной прибыли, юриспруденция, иранское право, мудараба